Some heavy metals and mineral nutrients of narrow endemic Cirsium byzantinum steud., from Istanbul, Turkey: Plant-soil interactions - (:unkn) unknown (Parlar Scientific Publications, 2018)
Cirsium species have economic importance because of their botanical and medicinal properties. Thus, this study has aimed to investigate some heavy metal (Fe, Mn and Zn) and mineral nutrient (B, Ca, K, Mg and Na) status of narrow endemic Cirisum byzantinum. Plant and soil element concentrations were analyzed by using ICP-OES and the evaluation of plant-soil interactions for heavy metals and mineral nutrients were carried out by statistical methods. The measured element concentrations (in mg/kg) were in ranges of 5.936-19.044 for B, 1862.161-4811.168 for Ca, 12.610-38.474 or Fe, 3421.383-6881.885 for K, 190.984-593.427 for Mg, 3.830-17.301 for Mn, 21.236-62.025 for Na, and 6.183-28.060 for Zn in plant parts. Statistical analysis for element interactions between root/leaf and co-located soil samples revealed that there a was positive correlation between B, Ca, Fe, K, Mg, Mn, Na and Zn found in soil and Na and Zn found in roots, and Fe, Mn and Na found in leaves, respectively. Herein, results of this study could provide preliminary knowledge for future studies to better understand element uptake and heavy metal accumulation status of endemic species. Also, this study could also provide some insights for responsible authorities to develop conservation strategies. © 2018 Parlar Scientific Publications. All rights reserved.
Keywords: Autecology; Cirsium; Conservation; Mineral nutrition; Plant-soil interactions